Optimalisasi Strategi Digital Marketing untuk Pengembangan Brand Produk Tenun Kelurahan Sandabilik, Tana Toraja - Nataniel Papalangi; Viktor Amos (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Woven fabric products from Sandabilik Village possess high cultural and economic value; however, they face challenges related to limited marketing reach, weak product branding, and low utilization of digital media. These constraints cause artisans to rely mainly on local markets. This community service activity aims to empower woven fabric artisans through digital marketing strategy assistance to strengthen product branding and expand market access. The activity involved a partner group of 20 woven fabric artisans in Sandabilik Village. The implementation methods included socialization sessions, training, and hands-on mentoring focused on product branding, digital content creation, and the use of social media and online marketplaces. The results indicate a significant improvement in participants’ understanding of digital marketing and branding concepts. Qualitatively, artisans were able to develop brand identities and independently create promotional content. Quantitatively, 85% of participants became capable of using social media for product promotion, and digital promotional reach increased by approximately 60% compared to pre-activity conditions. This program enhances artisans’ capacity to compete in an increasingly digital market environment.